Multifunctional Golf Facilities as a Resource of Important Ecosystem Services in a Changing Urban Environment: Nordic Case Studies. Issue 1 (19th October 2017) - Dahl Jensen, Anne Mette; Caspersen, Ole Hjorth; Jensen, Frank Søndergaard; Strandberg, Maria
Abstract : Multifunctional golf facilities are a resource of important ecosystem services in a changing urban environment. Several examples of multifunctional activities fulfilling environmental quality goals are available on Nordic golf courses. These examples should set the standard for many other peri‐urban golf courses. The handbook A Practical Guide to Assessing your Golf Course´s Multifunctional Potential (Jensen et al. 2015) is intended as a tool to visualize the multifunctional potential of golf facilities and to start the process of developing multifunctional values—for example, to contribute to the production or conservation of biological diversity, natural and cultural environments, and to the retention and expansion of ecosystem services in peri‐urban environments and the cultivated landscape. In this paper, we extract examples from Nordic multifunctional golf facilities and relate them to environmental quality goals.